Integrated Static Reservoir Modeling of Yan’an Formation, X-area, Ordos Basin, China - Loo, Sheau Huey (Universiti Teknologi PETRONAS, 2016)
The construction of a static reservoir model often requires integration of dataset from multidiscipline studies. However, for onshore X-area of Ordos Basin, only partial ready dataset is available for modeling activities. Thus, it is very crucial that sufficient dataset is generated and derived based on the limited data source. This main focus of this study will be divided into three (3) parts which are geophysical, petrophysical and geomodeling studies with aim to generate adequate data inputs for static model construction of X-area. In geophysical study, seismic interpretation had been done across the study area utilizing the 3D seismic data using PETREL 2013. Six depth converted horizons of Yan’an Formation, including Yan 6, Yan 7, Yan 8, Yan 9, Yan 10 and Chang 3 had been executed as the input for structural modeling of X-area. From petrophysical point of view, total of nine (9) wells from X-area had been evaluated. With application of well log correlation, Yan’an Formation is segregated into different zones and petrophysical analysis is performed specifically on each targeted zone with the aim to derive the essential petrophysical properties input needed for facies and petrophysical modeling. In order to increase the reliability of derived parameter, well log is further calibrated with core data. With X3 as the type well, GR log motif and core analysis had established that Zone 5 is dominated by crevasse splay; Zone 6 is chiefly deposited in floodplains; Zone 7, 8, and 9 is predominantly channelized sand facies. For geomodeling study, Object modeling and Sequential Indicator Simulation (SIS) technique are being utilized for channel and crevasse splay depofacies modeling respectively. Also, Sequential Gaussian Simulation (SGS) technique is being implemented in petrophysical modeling with aim to populate the derived porosity and permeability parameter into each modelled zone, honoring the well data and data transformation analysis. In terms of analogue studies in Malaysia, Jurassic-Cretaceous aged Payung Formation is certainly the best choice with its continental, fluviatile origin. Sedimentary logging and geological mapping on the analogue study area is accomplished to understand the inter-relationship between subsurface basin and the real outcrop analogue.